2011
DOI: 10.1186/1471-2474-12-18
|View full text |Cite
|
Sign up to set email alerts
|

Hyperadiponectinemia enhances bone formation in mice

Abstract: BackgroundThere is growing evidence that adiponectin, a physiologically active polypeptide secreted by adipocytes, controls not only adipose tissue but also bone metabolism. However, a role for adiponectin in bone development remains controversial.MethodsWe therefore investigated the endocrine effects of adiponectin on bone metabolism using 12-week-old male transgenic (Ad-Tg) mice with significant hyperadiponectinemia overexpressing human full-length adiponectin in the liver.ResultsIn Ad-Tg mice, the serum lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 35 publications
0
27
1
Order By: Relevance
“…While Shinoda et al48 found no abnormalities regarding bone mass and turnover in Ad-/Ad- mice, Williams et al49 as well as Oshima et al 50 found an increased bone density. Conversely, adiponectin overexpressing mice had increased bone mass, parameters of bone resorption and bone erosion were not affected 51. Contrary to what we would have expected based on our results, adenovirus-mediated systemic expression of human adiponectin in collagen-induced arthritis mice reduced clinical disease activity scores of collagen-induced arthritis 52.…”
Section: Discussioncontrasting
confidence: 95%
“…While Shinoda et al48 found no abnormalities regarding bone mass and turnover in Ad-/Ad- mice, Williams et al49 as well as Oshima et al 50 found an increased bone density. Conversely, adiponectin overexpressing mice had increased bone mass, parameters of bone resorption and bone erosion were not affected 51. Contrary to what we would have expected based on our results, adenovirus-mediated systemic expression of human adiponectin in collagen-induced arthritis mice reduced clinical disease activity scores of collagen-induced arthritis 52.…”
Section: Discussioncontrasting
confidence: 95%
“…The authors concluded that neither bone mass nor bone turnover is affected by increase in circulating adiponectin. In contrast, a study of 12-week-old males of two different lines of APN-Tg mice over-expressing human full-length adiponectin in the liver found a small increase in femoral BMD [39]. Circulating bone turnover markers and histomorphometric analysis of the tibia in this study found elevated osteocalcin, osteoblast surface and osteoid surface, whereas bone resorption parameters did not differ between APN-Tg mice and controls.…”
Section: Studies In Mice Over-expressing Adiponectinmentioning
confidence: 66%
“…One of these adipokines is adiponectin (APN) , which has been best known for its insulin‐sensitizing, anti‐inflammatory, and antiatherosclerotic properties . APN could partly regulate the bone marrow niche by its reported abilities to increase HSCs proliferation and to promote BMSCs differentiation toward the osteoblastic lineage . Furthermore, APN can stimulate the migration of different cell types including endothelial progenitor cells and cardiac fibroblasts .…”
Section: Introductionmentioning
confidence: 99%
“…A variety of in vitro and in vivo studies have demonstrated that APN can stimulate bone formation by a variety of mechanisms including: by signaling directly in osteoblasts to promote their differentiation , by favoring BMSCs differentiation toward the osteoblastic‐lineage , by decreasing the sympathetic tone and by inducing bone morphogenetic protein 2 (BMP‐2) production in osteoblasts . However, the putative role of APN in mobilizing BMSCs for bone wound healing has not yet been described.…”
Section: Introductionmentioning
confidence: 99%